The hidden power of secondary metabolites in plant-fungi interactions and sustainable phytoremediation - Elhamouly, Neveen Atta; Hewedy, Omar A.; Zaitoon, Amr; Miraples, Angelica; Elshorbagy, Omnia T.; Hussien, Suzan; El-Tahan, Amira; Peng, Deliang (Frontiers in Plant Science, 2022)
The global environment is dominated by various small exotic substances, known as secondary metabolites, produced by plants and microorganisms. Plants and fungi are particularly plentiful sources of these molecules, whose physiological functions, in many cases, remain a mystery. Fungal secondary metabolites (SM) are a diverse group of substances that exhibit a wide range of chemical properties and generally fall into one of four main family groups: Terpenoids, polyketides, non-ribosomal peptides, or a combination of the latter two. They are incredibly varied in their functions and are often related to the increased fitness of the respective fungus in its environment, often competing with other microbes or interacting with plant species. Several of these metabolites have essential roles in the biological control of plant diseases by various beneficial microorganisms used for crop protection and biofertilization worldwide. Besides direct toxic effects against phytopathogens, natural metabolites can promote root and shoot development and/or disease resistance by activating host systemic defenses. The ability of these microorganisms to synthesize and store biologically active metabolites that are a potent source of novel natural compounds beneficial for agriculture is becoming a top priority for SM fungi research. In this review, we will discuss fungal-plant secondary metabolites with antifungal properties and the role of signaling molecules in induced and acquired systemic resistance activities. Additionally, fungal secondary metabolites mimic plant promotion molecules such as auxins, gibberellins, and abscisic acid, which modulate plant growth under biotic stress. Moreover, we will present a new trend regarding phytoremediation applications using fungal secondary metabolites to achieve sustainable food production and microbial diversity in an eco-friendly environment.